Sludge-based activated carbon and its application in the removal of perfluoroalkyl substances: A feasible approach towards a circular economy. (May 2022) - Mohamed, Badr A.; Li, Loretta Y.; Hamid, Hanna; Jeronimo, Matthew
Abstract: This study explores the recovery of resources and energy from sewage sludge through the production of sludge-based activated carbon (SBAC) considering circular economy principles. The SBAC production costs were estimated under three scenarios considering various sludge dewatering/drying schemes to determine the production feasibility and its role in the circular economy. SBAC was tested in the removal of a mixture of nine commonly detected poly- and perfluoroalkyl substances (PFASs) in environmentally relevant concentrations of ∽50 μg/L in comparison to commercially available activated carbon (AC) using 5 mg of sorbent and 5 mL of a nine-PFAS mixture in deionised water. SBAC can be produced at approximately 1.2 US $/kg, which is substantially lower than the average production cost of commercial AC of >3 US $/kg. A net revenue ranging from 2 to 7 US $/kg SBAC was estimated by recycling the produced non-condensable gases and bio-oil to produce energy and selling the SBAC. Batch adsorption tests showed that the PFASs removal of SBAC was superior to that of granular AC and similar to that of powdered AC, reaching >91% to below the detection limit. The kinetics tests revealed that adsorption by SBAC and AC occurred within 15 min. The overall results demonstrate the potential of SBAC as an effective sorbent for PFASs, achieving waste-to-resources circular economy via resource and energy recovery from sewage sludge, eliminating sludge disposal and contaminant-leaching to the environment, and in enhancing the quality of wastewater effluent before discharge. Graphical abstract: Image 1 Highlights: Circular economy for WWTP, SBAC sorbent production and energy recovery were studied. Estimated SBAC production cost was 1.2 US $/kg with 2–7 US $/kg net revenue. SBAC effectively removed PFASs at environmentally relevant concentrations of ∽50 μg/L. SBAC out-performed commercial granular activate carbon (GAC) for PFAS removal. PFASs were rapidly removed by SBAC from aqueous solutions within 30 min.